Pengembangan Instrumen Kecerdasan Emosional Anak Usia Dini - Conita Ananto, Mafaza; Vinayastri, Amelia (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
Emotional intelligence is important to be instilled in children from an early age. The lack of compatibility of early childhood emotional intelligence instruments in achieving child development in the globalization era is a research problem. This study aims to develop an instrument of emotional intelligence for children aged 5-6 years. The method used to research and development modification of the Borg & Gall development model. The research populations were the teachers and parents of group B students. Sampling used incidental sampling technique. Research respondents amounted to 212 respondents. Content validity was carried out by experts, resulting in 6 dimensions of self-understanding, 5 dimensions of self-control, 5 dimensions of understanding others, and 6 dimensions of building relationships. The results of the study obtained the calculation of the validity of the field trial the percentage of teachers was 98% and the percentage of parents was 89%. The average value of the percentage of teachers and parents is 94% with a very valid category. Calculation of reliability using Cronbach's Alpha of 0.966 with a high reliable category. The findings of this study contribute to the understanding of early childhood emotional intelligence instruments and recommend early childhood educators use emotional intelligence instruments as a guide for assessing aspects of early childhood emotional development.